2021
DOI: 10.3390/medicina57090860
|View full text |Cite
|
Sign up to set email alerts
|

Cell Models for Chromosome 20q11.21 Amplification and Drug Sensitivities in Colorectal Cancer

Abstract: Background and objectives: The chromosome locus 20q11.21 is a commonly amplified locus in colorectal cancer, with a prevalence of 8% to 9%. Several candidate cancer-associated genes are transcribed from the locus. The therapeutic implications of the amplification in colorectal cancer remain unclear. Materials and Methods: Preclinical cell line models of colorectal cancer included in the Cancer Cell Line Encyclopedia (CCLE) collection were examined for the presence of amplifications in 20q11.21 genes. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous studies illustrated that miR‐1825 acts as a cancer‐promoting microRNA in numerous cancers, 16,21,43 however, the carcinogenic functions of miR‐1825 in HNSCC have not been ascertained yet. It has been shown that the 20q11.21 locus contains cancer‐associated genes with potential oncogenic properties, and amplification detected in this region in colorectal cancer leads to genomic instability and recurrent genetic abnormalities and contributes to cancer pathogenesis 44,45 . Jo et al found that copy number variation in the 20q11.21 region led to increased migration capacities, metastatic potential, aberrant differentiation tendencies, cell proliferation, and decreased sensitivity to apoptosis in many types of cancers and human pluripotent stem cells 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies illustrated that miR‐1825 acts as a cancer‐promoting microRNA in numerous cancers, 16,21,43 however, the carcinogenic functions of miR‐1825 in HNSCC have not been ascertained yet. It has been shown that the 20q11.21 locus contains cancer‐associated genes with potential oncogenic properties, and amplification detected in this region in colorectal cancer leads to genomic instability and recurrent genetic abnormalities and contributes to cancer pathogenesis 44,45 . Jo et al found that copy number variation in the 20q11.21 region led to increased migration capacities, metastatic potential, aberrant differentiation tendencies, cell proliferation, and decreased sensitivity to apoptosis in many types of cancers and human pluripotent stem cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the 20q11.21 locus contains cancerassociated genes with potential oncogenic properties, and amplification detected in this region in colorectal cancer leads to genomic instability and recurrent genetic abnormalities and contributes to cancer pathogenesis. 44,45 Jo et al found that copy number variation in the 20q11.21 region led to increased migration capacities, metastatic potential, aberrant differentiation tendencies, cell proliferation, and decreased sensitivity to apoptosis in many types of cancers and human pluripotent stem cells. 46 Given the facts that miR-1825 resides within 20q11.21 chromosomal region, where has been notified as a recurrent gain of function abnormality in human embryonic and induced pluripotent stem cells 13,14 and that 20q11.21 amplification in human embryonic stem cells resulted in acquisition of a geneexpression signature enriched for cancer-related genes, 16,17 we suggested that miR-1825 might promote cellular phenotypes related to cancer progression in HNSCC as well.…”
Section: Frem1 Is a Direct Target Of Mir-1825mentioning
confidence: 99%
“…CRISPR and RNAi dependency analysis identified YAP1 and JUP as recurrent gene dependencies in cell lines. Therefore, amplified 20q11.21 gene cell line models of CRC with resistance or sensitivity to various drug categories could be adopted within in vitro models to favor clinical drug development in this tumor [ 15 ].…”
mentioning
confidence: 99%